Social Media Monitoring, April-May 2020 - Ralston, Laura; Ali, Rabia (World Bank, Washington, DC, 2020)
There is a high level of knowledge on COVID-19, with most respondents aware of common symptoms and following preventative health measures. However, citizens face challenges maintaining social distancing recommendations when they need to purchase food and in their jobs. These challenges are more prevalent among lower income groups. Discussion on COVID-19 in social media spiked around the time large-scale social restrictions were introduced and common topics of conversation revolved around health care, food access, and job loss. Complementary survey data finds that these are citizens’ biggest concerns, over half indicated working fewer days, and about a quarter facing some level of food insecurity. While the overall tone in the discussions on social media and in online news sources has been moderating, the government handling of the situation is widely discussed, and survey respondents indicate concerns regarding social unrest and a wish for further government action.